This I Believe - Romulo, Carlos P. (Carlos Pena) (Tufts Archival Research Center, 2006)
Carlos Romulo describes his belief in being true to himself despite the cost, exemplified by his inability to be with his family while he operated the broadcast Voice of Freedom during WWII and in his decision to withdraw his candidacy for president of the Philippines in order to help a candidate who shared his values win the election.